Pengaruh TATO dan CR terhadap ROA pada Perusahaan Subsektor Food and Beverage yang Terdaftar di BEI - Lola Luthfi Aulia; Ruhadi Ruhadi; Diharpi Herli Setyowati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Research in this final task aims to find out and analyze the influence of TATO and CR on ROA on Food and Beverage Subsector companies listed on the IDX Period 2015-2019. The type of data used in this study is secondary data in the form of company financial statements. In this study, food and beverage companies on the Indonesia Stock Exchange that were used as research samples there were 8 companies. The research methods carried out are descriptive and quantitative research methods. The test was conducted using IBM SPSS. The methods used are with classical assumption tests, multiple linear regression analysis and hypothesis tests. The results of this analysis show that Total Assets Turnover has no effect on Return On Assets and Current Ratio has an effect on Return On Assets Total Assets Turnover and Current Ratio have a simultaneous effect on Retun On Assets.